Adsorption mechanism and valency of catechol-functionalized hyperbranched polyglycerols - Krysiak, Stefanie; Wei, Qiang; Rischka, Klaus; Hartwig, Andreas; Haag, Rainer; Hugel, Thorsten (Beilstein Journal of Organic Chemistry, 2015)
Nature often serves as a model system for developing new adhesives. In aqueous environments, mussel-inspired adhesives are promising candidates. Understanding the mechanism of the extraordinarily strong adhesive bonds of the catechol group will likely aid in the development of adhesives. With this aim, we study the adhesion of catechol-based adhesives to metal oxides on the molecular level using atomic force microscopy (AFM). The comparison of single catechols (dopamine) with multiple catechols on hyperbranched polyglycerols (hPG) at various pH and dwell times allowed us to further increase our understanding. In particular, we were able to elucidate how to achieve strong bonds of different valency. It was concluded that hyperbranched polyglycerols with added catechol end groups are promising candidates for durable surface coatings.
Keywords: adhesion; atomic force microscopy; catechol; hyperbranched polyglycerols; valency

Biological Adhesive Systems: From Nature to Technical and Medical Application - von Byern, J.; Grunwald, I. (Springer, 2010)

(untitled) - Krysiak, S.; Liese, S.; Netz, R. R.; Hugel, T. (J. Am. Chem. Soc., 2014)

Biological Adhesive Systems: From Nature to Technical and Medical Application - Silverman, H. G.; Roberto, F. F. (Byssus Formation in Mytilus, 2010)

(untitled) - Grunwald, I.; Rischka, K.; Kast, S. M.; Scheibel, T.; Bargel, H. (Philos. Trans. R. Soc. London, A, 2009)

(untitled) - Floriolli, R. Y.; von Langen, J.; Waite, J. H. (Mar. Biotechnol., 2000)

(untitled) - Zhao, H.; Waite, J. H. (J. Biol. Chem., 2006)

(untitled) - Waite, J. H.; Qin, X. (Biochemistry, 2001)

(untitled) - Papov, V. V.; Diamond, T. V.; Biemann, K.; Waite, J. H. (J. Biol. Chem., 1995)

(untitled) - Yu, J.; Wei, W.; Danner, E.; Ashley, R. K.; Israelachvili, J. N.; Waite, J. H. (Nat. Chem. Biol., 2011)

(untitled) - Lee, B. P.; Messersmith, P. B.; Israelachvili, J. N.; Waite, J. H. (Annu. Rev. Mater. Res., 2011)

(untitled) - Lee, H.; Scherer, N. F.; Messersmith, P. B. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Wang, J.; Tahir, M. N.; Kappl, M.; Tremel, W.; Metz, N.; Barz, M.; Theato, P.; Butt, H.-J. (Adv. Mater., 2008)

(untitled) - Wilke, P.; Helfricht, N.; Mark, A.; Papastavrou, G.; Faivre, D.; Börner, H. G. (J. Am. Chem. Soc., 2014)

(untitled) - Grandbois, M.; Beyer, M.; Rief, M.; Clausen-Schaumann, H.; Gaub, H. E. (Science, 1999)

(untitled) - Schmidt, S. W.; Beyer, M. K.; Clausen-Schaumann, H. (J. Am. Chem. Soc., 2008)

(untitled) - Schwaderer, P.; Funk, E.; Achenbach, F.; Weis, J.; Bräuchle, C.; Michaelis, J. (Langmuir, 2008)

(untitled) - Wei, Q.; Becherer, T.; Mutihac, R.-C.; Noeske, P.-L. M.; Paulus, F.; Haag, R.; Grunwald, I. (Biomacromolecules, 2014)

(untitled) - Wei, Q.; Becherer, T.; Noeske, P.-L. M.; Grunwald, I.; Haag, R. (Adv. Mater., 2014)

(untitled) - Hartwig, A.; Meissner, R.; Merten, C.; Schiffels, P.; Wand, P.; Grunwald, I. (J. Adhes., 2012)

(untitled) - Richter, K.; Diaconu, G.; Rischka, K.; Amkreutz, M.; Müller, F. A.; Hartwig, A. (Bioinspired, Biomimetic Nanobiomater., 2013)

(untitled) - Wei, Q.; Achazi, K.; Liebe, H.; Schulz, A.; Noeske, P.-L. M.; Grunwald, I.; Haag, R. (Angew. Chem., Int. Ed., 2014)

(untitled) - Wei, Q.; Krysiak, S.; Achazi, K.; Becherer, T.; Noeske, P.-L. M.; Paulus, F.; Liebe, H.; Grunwald, I.; Dernedde, J.; Hartwig, A.; Hugel, T.; Haag, R. (Colloids Surf., B, 2014)

(untitled) - Li, Y.; Qin, M.; Li, Y.; Cao, Y.; Wang, W. (Langmuir, 2014)

(untitled) - Yu, J.; Wei, W.; Menyo, M. S.; Masic, A.; Waite, J. H.; Israelachvili, J. N. (Biomacromolecules, 2013)

(untitled) - Bahri, S.; Jonsson, C. M.; Jonsson, C. L.; Azzolini, D.; Sverjensky, D. A.; Hazen, R. M. (Environ. Sci. Technol., 2011)

(untitled) - Li, S.-C.; Chu, L.-N.; Gong, X.-Q.; Diebold, U. (Science, 2010)

(untitled) - Sunder, A.; Hanselmann, R.; Frey, H.; Mülhaupt, R. (Macromolecules, 1999)

(untitled) - Sunder, A.; Mülhaupt, R.; Haag, R.; Frey, H. (Adv. Mater., 2000)

(untitled) - Roller, S.; Zhou, H.; Haag, R. (Mol. Diversity, 2005)

(untitled) - Pirzer, T.; Hugel, T. (Rev. Sci. Instrum., 2009)